Novel memory-based sensory approach to assess large-scale typicality: the case of mainland Portugal red wines - Jose-Coutinho, A. (2018)
Twenty professional wine experts were asked to describe their prototypical construct of a representative young red wine from each of the 12 Protected Geographical Indications (PGI) of mainland Portugal. No samples were assessed; the experiment was based on memory alone by completion of 12 extended self-reported sensory questionnaires. Four large-scale areas were differentiated, the typicality being statistically validated and described from a sensory standpoint. Alcohol, acidity, bitterness, and astringency were cross-linked; the respective variations were correlated with published literature and expressed as key factors for the regional macroscale area differentiation. Bitterness and astringency were found to be sensory different and related on a geographical scale, as bitterness was primarily affected by inland/coastal influence; while astringency confirmed its customary north/south dependence that finding is to be considered a new understanding. Moreover, with the proposed methodology, it was possible to achieve a novel nationwide sensory characterization of PGIs, overcoming present day limitations on macroscale sensory research and sample representativeness. Results by uncalibrated prototypical memory assessment of single PGI Beira Atlântico were compared with the outcome of calibrated wine sampling assessment by local experts, using the same sensory questionnaire, and were found significantly correlated. The need for a calibration stage was found uneven regarding the overall group of scrutinized wine descriptors.